Study of Activation Energy of Magnetohydrodynamic Radiative Casson Nanofluid With Darcy-Forchheimer Flow and Cattaneo-Christov Heat Flux Model - Younus, Mohammed; Venkatalakshmi, A.; Ramesh, Vajja (Communications in Mathematics and Applications, 2023)
In the present paper, the Activation Energy (AE) of a radiative magnetohydrodynamic (MHD) Casson nano fluid with Darcy-Forchheimer flow, and Cattaneo-Christov heat flux model across a linearly stretched sheet under convective boundary conditions was numerically explored. The influence of different factors on profiles of temperature, velocity, and concentration was investigated and graphically interpreted. The acquired results are extremely similar to those found in the open literature. The profile of velocity was observed for porosity parameter, Casson fluid parameter, Forchheimer parameter, and magnetic parameter. The temperature profile was observed for porosity parameter, Forchheimer parameter, Brownian motion parameter, magnetic parameter, thermophoresis parameter, Casson fluid parameter, Biot number, thermal relaxation parameter, and radiation parameter. The concentration profile was examined for porosity parameter, Activation Energy (AE), temperature difference, thermophoresis parameter, chemical reaction rate constant, parameter of Brownian motion, and Lewis number. Also, local Nusselt number, coefficient of skin friction, and local Sherwood number were found for different parameters.
Keywords: Activation energy; Casson nano fluid; Darcy-Forchheimer flow; Shooting method; Cattaneo-Christov heat flux